Anatomical considerations of the iliac crest on percutaneous endoscopic discectomy using a transforaminal approach. - Tezuka, Fumitake; Sakai, Toshinori; Abe, Mitsunobu; Yamashita, Kazuta; Takata, Yoichiro; Higashino, Kosaku; Chikawa, Takashi; Nagamachi, Akihiro; Sairyo, Koichi (Spine Journal, 2017)
Background Context: Percutaneous endoscopic discectomy is a minimally invasive procedure for the surgical treatment of lumbar disc herniation (LDH). It can be performed under local anesthesia and requires a skin incision of only 8 mm, with minimal disruption of the spinal structures including ligaments and muscles. However, performing percutaneous endoscopic discectomy with a transforaminal approach (TF-PED) for the lower lumbar spine is associated with some anatomical problems, such as interference from the iliac crest. This study sought to assess the operability of TF-PED for the lower lumbar spine.Purpose: The purpose of this study was to assess a three-dimensional relationship between the trajectory of TF-PED and the iliac crest, and the operability of TF-PED at the lower lumbar disc levels (L4-L5 and L5-S1) using CT images.Study Design: This is a retrospective study using 323 multiplanar abdominal computed tomography (CT) scans.Patient Sample: We retrospectively reviewed contrast-enhanced multiplanar abdominal CT scans of 323 consecutive patients (203 male and 120 female) in our hospital from April 2009 to March 2013. The mean age was 66.5 (range 15-89) years old.Outcome Measures: The operability of the TF-PED was the outcome measure.Materials and Methods: We defined the tangent line in the iliac crest and the superior articular process of the caudal spine as the trajectory line of TF-PED, and evaluated the maximum inclination angle of the trajectory of the TF-PED (α angle) at the L4-L5 and the L5-S1 disc levels. Assuming the use of an oblique viewing endoscope at 25°, we defined α angle≥65° as the operability of TF-PED.Results: (1) Relationship between iliac crest and disc level: The trajectory of the TF-PED interfered with the iliac crest at L4-L5 in 40.2% (right) and 54.5% (left) of the subjects, and at L5-S1 in 99.7% and 100% of the subjects. (2) The maximum inclination angle of the trajectory of TF-PED: the α angles were 84.3° and 82.3° at the L4-L5, and 56.8° and 55.2° at L5-S1. (3) Laterality of the α angle: At both disc levels, the mean age of the subjects with a laterality of ≥10° was significantly higher than that of subjects with a laterality of <10°. (4) Operability of TF-PED: At L4-L5, TF-PED could be performed in 94.4% and 90.4% of the subjects. In contrast, at L5-S1 the procedure could be performed in 24.1% and 19.2% of the subjects (male: 15.8% and 10.8%, female: 38.3% and 33.3%).Conclusions: From the results of this study, the trajectory of TF-PED can be limited by the surrounding anatomical structures. The maximum inclination angle indicated that treatment for the central type of LDH at the L5-S1 disc level was considered more difficult than that at the L4-L5 disc level because of the iliac crest. In the clinical setting, such anatomical particularities can be overcome by using a more perpendicular approach (hand-down technique) with the possible addition of a foraminoplasty. Moreover, we found that we must consider the laterality of the trajectory of TF-PED in terms of the patients' age or sex.